ALHAZEN BILLIARD PROBLEM SOLUTION FOR PARALLELOGRAM - NULHAKIM (NIM: 90114014), IMAM
The problem is variation form of Alhazen Billiard Problem. If there is parallelogram shaped table, say it ABCD with AB k CD and a white ball at one side of billiard table, call it P point. The question will be answer is eksist Q point at BC side if white ball shoot to Q point, then the white ball will bounce to another side and back to P point. In this disertation, give an equirement distance P to A, wich parameter is DAB and long side AB who could be garante eksist Q point.